2018
DOI: 10.1186/s13195-018-0393-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-word comprehension deficits in the nonfluent variant of primary progressive aphasia

Abstract: BackgroundA subset of patients with the nonfluent variant of primary progressive aphasia (PPA) exhibit concomitant single-word comprehension problems, constituting a ‘mixed variant’ phenotype. This phenotype is rare and currently not fully characterized. The aim of this study was twofold: to assess the prevalence and nature of single-word comprehension problems in the nonfluent variant and to study multimodal imaging characteristics of atrophy, tau, and amyloid burden associated with this mixed phenotype.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…In logopenic variant PPA, research has identified three different subvariants based on core deficits of (i) single-word comprehension, (ii) repetition, and (iii) confrontation naming, each associated with specific atrophy profiles [14•]. Moreover, vocabulary loss (a core feature of svPPA) may be relatively common in nfvPPA [15]. A lack of understanding of the underlying pathophysiology in PPA syndromes is a common theme that makes principled diagnostic classification difficult.…”
Section: The Challenge Of Clinical Diagnosis: Detection and Definitionmentioning
confidence: 99%
“…In logopenic variant PPA, research has identified three different subvariants based on core deficits of (i) single-word comprehension, (ii) repetition, and (iii) confrontation naming, each associated with specific atrophy profiles [14•]. Moreover, vocabulary loss (a core feature of svPPA) may be relatively common in nfvPPA [15]. A lack of understanding of the underlying pathophysiology in PPA syndromes is a common theme that makes principled diagnostic classification difficult.…”
Section: The Challenge Of Clinical Diagnosis: Detection and Definitionmentioning
confidence: 99%
“…In MV, object recognition and comprehension deficits exist in combination with distorted speech or agrammatism (Mesulam et al, 2014(Mesulam et al, , 2012. In SV and MV, semantic distractors related to the more dominant meaning of a homonym were the prime source of errors during single-word comprehension (Schaeverbeke et al, 2018), suggesting a shared mechanism. When directly comparing between PPA subtypes, semantic errors were common in all subtypes, whereas circumlocutions were more frequent in LV and SV versus speech production errors in NFV (Budd et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…were included in previously published work (Grube et al, 2016;Nelissen et al, 2011;Schaeverbeke et al, 2018). Twenty-four healthy controls (HC), matched for age, gender and education (…”
Section: Introductionmentioning
confidence: 99%
“…), in combination with neurolinguistics assessment and clinical MRI, as well as, where available, will not be discussed further because of the smaller sample size compared to the NFV and SV groups. Of the 12 NFV cases, all exhibited AOS on clinical examination and 5 patients (case 20-23 and 31) also displayed single-word comprehension deficits upon testing and would also fit the more recently described criteria for the "mixed variant" 2,29 . All patients received a volumetric MRI scan and 7 NFV and 7 SV DTI imaging.…”
Section: Participantsmentioning
confidence: 72%
“…The LV group will not be discussed because of the smaller sample size compared to the NFV and SV groups. All NFV cases clinically exhibited AOS (“effortful speech”) and 5 patients (case 20-23 and 31) also displayed clinically relevant single-word comprehension deficits early in the disease and would also fit the more recently described criteria for the “mixed variant” (Mesulam et al, 2014; Schaeverbeke et al, 2018). It is of note that this subtype was described after enrollment for our study started.…”
Section: Methodsmentioning
confidence: 79%